Determinants of firm boundaries and organizational performance: an empirical investigation of the Chilean truck market - Christian Balcells (Journal of Evolutionary Economics, 2022)
The boundaries of a firm, particularly those of manufacturers that import heavy-duty Class 8 trucks and tractors into the Chilean automotive market, depend on economizing transaction costs. This empirical study investigates the vertical integration of these manufacturers and their respective dealers. By conducting a transaction cost analysis, this study results in two distinct cases. For the first case, the generalized linear models' estimations and hypothesis tests for the count data of the 'types of units sold' consider the firms' specificity as emissions standards, asset specificity as brand culture, and firms' endowments as offering finance for their dealers. The second case examines environmental uncertainty with respect to dynamic indicators that interfere with manufacturers' external transaction-based efficiency. Overall, the results strengthen transaction cost theory, suggesting that European manufacturers with vertical integrated structures economize on brand reputation, while their industry competitors derive gains from uncertainty of the exchange rate. The evolution of their boundaries coincides with the immediate adaptations of price of the truck, uncertainty concerning the demand for Chile's leading export commodity, and technology uncertainty of emissions regulations. To reduce transaction costs, manufacturers avoid the production of off-assembly-line trucks and tend to circumvent integration with their dealers through investments.
Keywords: B52; D23; D22; 330; Vertical integration; Transaction cost analysis